2010
DOI: 10.1007/s00535-010-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

The multidrug-resistance protein 4 polymorphism is a new factor accounting for thiopurine sensitivity in Japanese patients with inflammatory bowel disease

Abstract: These results suggest that MRP4 G2269A might be a new factor accounting for thiopurine sensitivity in Japanese patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 29 publications
0
95
1
Order By: Relevance
“…Direct sequence analyses in our laboratory indicated that the allelic frequency of MRP4 G2269A was 14.7% in the Japanese population (24). In IBD patients treated with AZA/6-MP, the WBC count was significantly lower in patients with the MRP4 G2269A SNP than in patients with a wild allelotype (24).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Direct sequence analyses in our laboratory indicated that the allelic frequency of MRP4 G2269A was 14.7% in the Japanese population (24). In IBD patients treated with AZA/6-MP, the WBC count was significantly lower in patients with the MRP4 G2269A SNP than in patients with a wild allelotype (24).…”
Section: Introductionmentioning
confidence: 77%
“…In particular, Japanese populations are sensitive to thiopurines, and relatively lower doses of AZA (0.6-1.2 mg/kg/day) are recommended for the treatment of Japanese IBD patients (11). Similar to TPMT A719G and ITPase C94A, we recently showed that MRP4 G2269A is a new factor accounting for heightened thiopurine sensitivity in Japanese patients with IBD (24). Although the SNPs accounting for thiopurine sensitivity have been reported as important factors for individualizing therapy to minimize adverse effects and to maximize clinical response, a rapid and clinically applicable method for the SNP genotyping of these genes has not yet been established.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In 403 patients with breast cancer, cyclophosphamide-induced adverse drug reactions were associated with ABCC4 polymorphisms [168], and the c.2269A allele of ABCC4 was associated with significantly lower white blood cell counts and with higher erythrocyte content of 6-thioguanine nucleotide in a cohort of 235 patients suffering from inflammatory bowel disease [169].…”
Section: Later a Study In 95 Caucasians Reported 74 Variations Includmentioning
confidence: 99%
“…Studies show that single nucleotide polymorphisms (SNPs) in the inosine triphosphate pyrophosphatase (ITPA) locus are associated with anemia in patients treated with combination therapy (12)(13)(14). Two SNPs that are associated with ITPA enzyme activity were identified in the Caucasian population (12), but the Japanese population lacks one of these SNPs (14,15). A limited number of reports have demonstrated the association of ITPA genotypes with RBV-induced anemia, but further studies concerning the role of ITPA genotypes on RBV-induced anemia are required.…”
mentioning
confidence: 99%